Learning and teaching styles: Empowering diverse learners in tertiary classrooms - Dreyer, Carisma (Koers, 1996)
Learning and teaching styles: Empowering diverse learners in tertiary classroomsThe aim of this article is to make lecturers aware of the importance of the various elements comprising an individual learning and teaching style. Suggestions are made as to how lecturers can help their students develop a more flexible, empowered approach to diverse learning contexts and tasks and thereby preventing "style wars". If lecturers can show students the variety and versatility of learning styles by pro v id in g experiences in different teaching styles, the resulting awareness and expansion of student learning styles may better allow students to meet the demands of academic teaching methods and assignments.